Prototipe Teknik Mutual Authentication Untuk Digital Rights Management - Setyoko, Yoso Adi; Zafia, Anggi; Utomo, Aulia Desy Nur (LPPM UNIKA Santo Thomas, 2022)
Our research is the adoption of mutual authentication techniques on smart cards for Digital Rights Management (DRM) which is applied using network protocol engineering. We adopted the protocol engineering from the mutual authentication technique owned by the Mifare Desfire smart card. The tests carried out in our research are testing the security aspects of authentication and data confidentiality. Our authentication test is done by changing the client and server master keys that determine the success of authentication. Meanwhile, data confidentiality testing is carried out by tapping data sent from the client to the DRM server. When authentication by the client and server fails, the software is declared invalid and vice versa. The result of our research is the successful implementation of the adoption of the smart card's mutual authentication technique for application protection in DRM including authentication and encryption functions.